The feeding peculiarities of the Antarctic seals in the region of the Argentina Islands Archipelago - I. Dykyy (Ukrainian Antarctic Journal, 2009)
The detailed analysis of a food of the Antarctic species of seals around Argentine islands archipelago, that was spent through out 11 Ukrainian Antarctic expedition (2006-2007), has shown that krill (Euphausia superba) is the main type of food for the major species of seals in region. Krill makes 97,2 % to a diet of fur seals (Arctocephalus gazella) and 90 % to a diet crabeater seal (Lobodon carcinophagus) during the summer period. It is established rather big dimensional and weight rates to young growth in comparison with literary data àccording to Weddell seal (L. weddelli) newborns monitoring. It testifies to enough qualitative and sufficient forage reserve for pregnant Weddell seal females in archipelago water area in which diet krill prevails also (about 70 %). Considering that from 5 seals species counted within archipelago, the most numerous is the crabeater seal and a southern fur seal - these species can be used as «species indicators» of krill distribution and quantity in the given region. It is established, that the leopard seal's fodder diet is similar, to a diet of a specie around eastern Antarctic, despite an essential latitude difference of specie habitat arrangements. The trophical researches of Weddell seal have allowed to define a new commercial specie of large squid Psychroteuthis glacialisfor the first time in given region. These results have great value not only for a definition of an actual condition of Antarctic ecosystem and biovariety preservations in planetary scale. But also can be used for working out of the management project for future rational use of krill sea stocks and squids in the given region of Antarctic, at the state level.